Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1038/339317a0
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile intracellular calcium release does not depend on fluctuations in inositol trisphosphate concentration

Abstract: Many hormones, neurotransmitters and growth factors evoke in their target cells oscillations in the free internal Ca2+ concentration [( Ca2+]i). In electrically non-excitable cells these fluctuations are due to periodic release of Ca2+ from intracellular reservoirs, stimulated by the internal messenger inositol trisphosphate (InsP3). Most models at present invoke fluctuating levels of InsP3 as a key component in generating the oscillations in [Ca2+]i. InsP3 injected into intact cells evokes irregular and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
188
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 335 publications
(205 citation statements)
references
References 27 publications
17
188
0
Order By: Relevance
“…Sensitivity of the inositol 1,4,5-trisphosphate receptor to IP 3 varies widely under different conditions. In vitro studies report sensitivity that varies considerably with the cell type (45)(46)(47), with affinities in the nanomolar range in hepatocytes (48), pancreatic acinar cells (49,50), and smooth muscle (51) but an EC 50 of 25 M in neurons in controlled cytoplasmic environments (52) and intact cell bodies (21,50,53). In experiments on non-neuronal cells, up to 10 M single-caged IP 3 has been used, a concentration that does not activate or block calcium release (12).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity of the inositol 1,4,5-trisphosphate receptor to IP 3 varies widely under different conditions. In vitro studies report sensitivity that varies considerably with the cell type (45)(46)(47), with affinities in the nanomolar range in hepatocytes (48), pancreatic acinar cells (49,50), and smooth muscle (51) but an EC 50 of 25 M in neurons in controlled cytoplasmic environments (52) and intact cell bodies (21,50,53). In experiments on non-neuronal cells, up to 10 M single-caged IP 3 has been used, a concentration that does not activate or block calcium release (12).…”
Section: Discussionmentioning
confidence: 99%
“…High amplitude, aberrant, intracellular Ca 2ϩ waves that propagate from the apical to basolateral region of the acinar cell predispose to early features of pancreatitis, particularly intra-acinar protease activation (8,9). We know that intracellular Ca 2ϩ release is responsible for the onset of this aberrant Ca 2ϩ signal (10). In addition, we have previously shown that the ryanodine receptor (RYR), 4 a major intracellular Ca 2ϩ channel, is localized to the basolateral region of the acinar cell and, more importantly, is linked to the onset of pathologic protease activation (8).…”
Section: From the Yale University School Of Medicine New Haven Connmentioning
confidence: 99%
“…In both steady-state and luminal potential models, continuous activation of InsP 3 receptor channels by a constant concentration of InsP 3 [36] and/or openings of other 'leak' channels [37,38] are required for self-sustained oscillation. It may also be argued that such constant openings of Ca 2+ releasing channels are not enough for optimal Ca 2+ release.…”
Section: Ca 2+ Oscillation By 'Quantal' Ca 2+ Releasementioning
confidence: 99%